(untitled) (Comunicação & Inovação, 2018)
Analysis of the channels maintained by health professionals in YouTube Brazil, under Thompson’s new visibility concept, focusing on the occupation of media spaces by these professionals and their direct communication with the public, as opposed to the minor use that communication vehicles and professionals specializing in health make of the platform. Exploratory research conducted between May 1st and August 1st, 2017 on YouTube Brazil health channels, identifying the main characteristics of the products and their communication strategies.